(untitled) (Italian Review of Legal History, 2024)
These notes intend to illustrate the background of the conference commemorating the Piazza Loggia massacre in Brescia (28 May 1974), organized thanks to the synergy between the University, cultural institutions and the social fabric of the city, and held at the Department of Law. It was animated by two witnesses of that human and civil tragedy, and two important legal historians: massacres, subversion, terrorism, State and deviant apparatus, truth, justice and civil society are some of the themes which, valorizing memory through history, were addressed in the contributions to the conference, which have now been given a written form in this review.